Synthesis of magnetic nanoparticles to detect Sudan dye adulteration in chilli powders. (30th November 2019) - Yu, Xi; Lee, Jun Kang; Liu, Huilin; Yang, Hongshun
Highlights: Fe3 O4 magnetic nanoparticles were grafted with polymer coating. Magnetic extraction approach was used for Sudan dyes in chilli powders. A novel detection method for Sudan dyes was developed. The method was used to analyse Sudan dyes in chilli powders highly sensitively. Abstract: Magnetic nanoparticles were synthesised to extract Sudan dyes from chilli powders. The adsorbents used were magnetic ferroferric oxide nanoparticles coated with polystyrene. The extraction procedures for Sudan dyes comprised liquid-solid extraction and magnetic solid phase extraction. The conditions were optimised to achieve efficient magnetic solid phase extraction, including extraction and desorption time, type and volume of the desorption solvent, and the mass of the adsorbents. Repeatability tests showed satisfactory recovery rates of 80.2–115.8%, with a relative standard deviation <3.8%. The results suggested that the proposed extraction method was effective and efficient to extract Sudan dyes from chilli powders. The extraction process was simpler compared with traditional approaches because the adsorbents can be rapidly removed from the sample matrix using a permanent magnet. The use of recyclable adsorbents decreased the cost greatly. Chilli powder samples collected from local markets in Singapore were tested using the proposed method under optimum conditions.